INTRACARDIAC ECHOCARDIOGRAPHY: AN EXTRAORDINARY TOOL TO ABLATE TYPICAL ATRIAL FLUTTER. - Khan, Imran; Shah, Bakhtawar; Awan, Zahid Aslam (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the role of intra cardiac echocardiography in ablating typical atrial flutter. Methodology: This cross sectional study was conducted in the Department of Cardiology, Hayatabad Medical Complex, Peshawar from June 2006 to June 2018. All patients with typical atrial flutter were included while those with atypical atrial flutter and scar related flutter were excluded. ICE was used in 06 cases. Conventional five wire study was performed. Cavotricuspid isthmus (CTI) was located electro anatomically using fluoroscopic or with the help of intra cardiac echocardiography (ICE) guidance. Ablation was done using standard protocols with 60 degree Celsius temperatures and 40-50 watts power in case of use of therapy catheter. In case of irrigated cooled tip catheter, the flow was kept at 30 ml/hour and the power at 30 watts. CTI was ablated and booster burns applied. Trans-isthmus conduction time and bidirectional block was documented. The data were analyzed using SPSS version 23. Results: Out of 1738 cases of different arrhythmias admitted for elective ablation, 48 cases were typical flutter. All the 6 cases that were ablated with ICE guidance had lesser procedure time and flouro time with better success and low recurrence. Conclusion: Intracardiac echocardiography (ICE) has athe capability to reveal the anatomy of the cavotricuspid isthmus and guide ablation in difficult cases.